Interfacial strength and deformation mechanism of SiC–Al composite micro-pillars. (15th March 2016) - Guo, Xiaolei; Guo, Qiang; Li, Zhiqiang; Fan, Genlian; Xiong, Ding-Bang; Su, Yishi; Zhang, Jie; Gan, Chee Lip; Zhang, Di
Abstract: A comprehensive understanding of the interfacial properties in particle-reinforced metal matrix composites (PRMMCs) requires an accurate determination of the cohesive strength of the interface. In this study, micro-pillars containing a slanted SiC/Al interface were fabricated, and were tested by uniaxial compression. The interfacial shear strength was found to be 133 ± 26 MPa, consistent with values predicted by numerical simulations. The stress–strain response of the composite pillars was characterized by shorter strain bursts and more significant strain hardening, as compared with their monolithic Al counterparts. These observations were interpreted by grain fragmentation and dislocation pile-up at the SiC/Al interface upon deformation. Graphical abstract: Measurement of shear strength of SiC/Al interface.